Dietary diversity and evolution of the earliest flying vertebrates revealed by dental microwear texture analysis - Jordan Bestwick (Nature Portfolio, 2020)
Microwear patterns on teeth can be used to infer diet as different foods leave different marks. Here, Bestwick and colleagues analyse microwear from the teeth of pterosaurs—extinct flying reptiles colloquially known as “pterodactyls”—to reconstruct their dietary diversity and evolution.